Characterization of the Human Pancreas Side Population as a Potential Reservoir of Adult Stem Cells. Issue 1 (January 2018) - Augstein, Petra; Loudovaris, Thomas; Bandala-Sanchez, Esther; Heinke, Peter; Naselli, Gaetano; Lee, Lily; Hawthorne, Wayne J.; Góñez, L. Jorge; Neale, Alana M.; Vaillant, François; Thomas, Helen E.; Kay, Thomas W.; et al.
Abstract : Objectives: The side population (SP) contains cells with stem cell/progenitor properties. Previously, we observed that the mouse pancreas SP expanded after pancreatic injury. We aimed to characterize the SP in human pancreas as a potential source of stem cells. Methods: Human organ donor pancreata were fractionated into islets and exocrine tissue, enriched by tissue culture and dispersed into single cells. Cells were phenotyped by flow cytometry, and the SP was defined by efflux of fluorescent dye Hoechst 33342 visualized by ultraviolet excitation. Cells were flow sorted, and their colony-forming potential measured on feeder cells in culture. Results: An SP was identified in islet and exocrine cells from human organ donors: 2 with type 1 diabetes, 3 with type 2 diabetes, and 28 without diabetes. Phenotyping revealed that exocrine SP cells had an epithelial origin, were enriched for carbohydrate antigen 19-9 + ductal cells expressing stem cell markers CD133 and CD26, and had greater colony-forming potential than non-SP cells. The exocrine SP was increased in a young adult with type 1 diabetes and ongoing islet autoimmunity. Conclusions: The pancreatic exocrine SP is a potential reservoir of adult stem/progenitor cells, consistent with previous evidence that such cells are duct-derived and express CD133. Abstract : Supplemental digital content is available in the text.